Gamified Android-Based Academic Information System - Henry Setiana; Seng Hansun (Institute of Advanced Engineering and Science, 2017)
Student is often lazy when it comes to studying, and how to motivate student was one of the problem in the educational world. To overcome the matters, we will implement the gamification method into an Academic Information System. Academic Information System is a software used for providing information and arranging administration which connected with academic activities. By implementing the gamification method, it is expected to improve student’s interest on the study programs. Gamification itself is a process with the purpose of changing non-game context into a more interesting application by integrating game thinking, game design, and game mechanics. From the evaluation result, it is concluded that the application has been successfully built and the gamification method has been successfully implemented to improve student’s interest and the most influential gamification features are point and reward.